EGFR polymorphisms drive lung cancer risk and survival disparities: a genotype-expression-outcome cohort study - Chao Zuo; Ziqiang Wang; Yi Liu; Jing Cheng; Dongli Yang; Yu Wang; Yongchao Qiao (Frontiers in Genetics)
PurposeTo investigate the correlation between single-nucleotide polymorphisms (SNPs) of the Epidermal growth factor receptor (EGFR) gene and its protein expression with susceptibility and survival prognosis of lung cancer (LC) patients.MethodsUsing SNP-scan high-throughput technology, the EGFR gene’s rs2227983, rs2293347, and rs884225 locations were analyzed in 300 LC patients and 150 healthy individuals. And small cell lung cancer (SCLC), lung adenocarcinoma (LUAD), and lung squamous carcinoma (LUSC) were subdivided into groups for lung cancer patients. Chi-square test and logistic regression analysis were used to assess the susceptibility of LC. The correlation between SNP haplotypes and LC risk was analyzed using the SHEsis website. KM curves and Cox regression were used to analyse the association between polymorphisms and survival prognosis of LC patients. Expression differences in protein levels were analyzed using immunohistochemistry.ResultsEGFR rs2293347 was associated with LUAD, LUSC, and SCLC susceptibility, and rs884225 was associated with LUAD susceptibility. Haplotype ATT was associated with LC and histological type LUAD and SCLC susceptibility. Meanwhile, rs2293347-TT and rs884225-TT were associated with worse prognosis, and rs2293347-TT was an independent risk factor for prognosis in patients with LC. Furthermore, tumor tissue EGFR protein levels were elevated in patients with both genotypes.ConclusionEGFR rs2293347 (pan-subtype) and rs884225 (LUAD-specific) polymorphisms increase LC risk through elevated protein expression, with rs2293347-TT conferring worse survival. These genotype-protein correlations highlight their dual role as susceptibility markers and prognostic predictors in precision oncology.